2015
DOI: 10.1080/01639625.2014.977159
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Perceptions and Experiences of Bullying by Race and Ethnicity among Middle School Students in the United States

Abstract: Little is known about how ethnic identity influences bullying. Using a racially diverse sample, we examine how within-race perceptions match experiences. We utilize bivariate probit regression to examine the correlation between actual and perceived victimization and bullying experiences. Results suggest no differences in victimization by ethnicity but perceived victimization differed across groups. Perceived and actual bullying differed across all groups. School climate acted as a protective factor against bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 44 publications
1
18
1
2
Order By: Relevance
“…This could be because boys are less likely to consider cyberbullying a problem when compared with girls (Agatston et al, 2007; Holfeld & Grabe, 2012; Mishna et al, 2009). In addition, boys could be less sensitized to the issues related to cyberbullying than girls, in part because they are less likely to engage in cyberbullying (Connell et al, 2014) or because the types of harms related to cyberbullying may be less damaging to boys than to girls. For example, girls’ reputations can be more damaged after pornographic pictures of them have been shared or posted online.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because boys are less likely to consider cyberbullying a problem when compared with girls (Agatston et al, 2007; Holfeld & Grabe, 2012; Mishna et al, 2009). In addition, boys could be less sensitized to the issues related to cyberbullying than girls, in part because they are less likely to engage in cyberbullying (Connell et al, 2014) or because the types of harms related to cyberbullying may be less damaging to boys than to girls. For example, girls’ reputations can be more damaged after pornographic pictures of them have been shared or posted online.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Mike and Mukhtar (2016) studied bullying and racism among school-age children in Asia and Great Britain. Nevertheless, it is important to emphasize from the theoretical review carried out -and in coherence with what was pointed out by Connell et al (2015) -that in Latin America little research was found on school intimidation specifically in racism related to an ethnic group.…”
Section: Racial Intimidation At Schoolmentioning
confidence: 59%
“…It can also be related to the fact that students do not completely transform their cultural identity (Mendez et al, 2016) to avoid social prejudice and to adapt to the settlers' demands. As a result, the study revealed that the cultural diversity of Amazonas is threatened by racial school intimidation because this might generate the disappearance of some beliefs, languages, customs and traditions (Connell et al, 2015). Notwithstanding, one of the limitations of the study is not including parents, teachers and parents as participants, because listening all the voices of the system is relevant to understand this phenomenon (Boulanger, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Αν και στην παρούσα έρευνα δεν εξετάζεται αναλυτικά ο ρόλος των εκπαιδευτικών, αξίζει να σημειωθεί, ότι η καλή σχέση και συνεργασία μεταξύ των μαθητών/-τριών και των εκπαιδευτικών βοηθά στη μείωση του φαινομένου του εκφοβισμού/ θυματοποίησης. Ανεξάρτητα από τα σχολικά προγράμματα, αυτού του είδους οι παρεμβάσεις των εκπαιδευτικών, μπορούν να δημιουργήσουν ένα πιο ασφαλές και θετικό σχολικό περιβάλλον για όλους τους μαθητές (Connell, El Sayed, Gonzalez, & Schell-Busey, 2015). Επιπλέον, σύμφωνα με τη βιβλιογραφία σε σχολεία, όπου οι εκπαιδευτικοί παρεμβαίνουν σε περιστατικά εκφοβισμού και οι μαθητές/-τριες έρχονται αντιμέτωποι με τις συνέπειες των πράξεων τους, τότε έχουν περισσότερες πιθανότητες να συμπεριφερθούν σωστά, ακόμα και όταν δεν υπάρχει επίβλεψη από τους εκπαιδευτικούς (Powers & Swick, 2014).…”
Section: η επίδραση της εθνοπολιτισμικής προέλευσης στους κοινωνιοψυχολογικούς παράγοντες που συνδέονται με τους τρόπους με τους οποίους unclassified